Damage mechanism and protection measures for Yanchang shale Chang 7 reservoir, China - Lin, Penghao (Frontiers in Earth Science, 2025)
The Yanchang shale is a key resource in the Ordos Basin of Shaanxi, China. To optimize its extraction and production, it is crucial to understand formation damage mechanisms and implement effective solutions. In this study, shale samples were analyzed for mineral composition and microstructure using X-ray diffraction and scanning electron microscopy. Hydration characteristics were evaluated through inhibition tests, and the water contact angle on the shale was measured. Changes in shale permeability were determined via pressure transmission tests. The results identified that water blocking, polymer intrusion, water sensitivity and salt sensitivity as the primary causes of reservoir damage. To address these issues, a surfactant was proposed to modify core wettability and eliminate water blockage, while an enzyme was suggested to prevent polymer wrapping and clogging. Incorporating these additives can lead to the development of low-damage fracturing fluid systems that enhance performance.